Kebijakan Ekonomi Khalifah Umar Ibn Khatab - Khamidiyah, Lailun Nurul; Syafi'i SJ, Ahmad; Ayu, Diyan Putri (Indonesian Journal of Islamic Economics and Finance, 2021)
Economics is an activity that can be said to be the same as human existence on this earth, so that then economic motives arise, namely a person's desire to fulfill his life needs. Economic principles are steps taken to meet needs with certain sacrifices to obtain maximum results. During the reign of Caliph Umar, the issue of zakat was not an issue. Even because there are many people who pay zakat, they can form councils, including military councils, social security for providing wages to employees. In this paper contains three problems. How was the economic condition of the people during the leadership of Caliph Umar, what were the forms of economic policy of Caliph Umar, and how was the influence of Umar's economic policies?. This research uses library research method (library research). The data sources used by the author are mainly primary and secondary sources. Then the author will analyze the data using a descriptive method, which is to determine the interpretation of the data collected in the form of rich words, not numbers. Based on the results of the study, it can be concluded that the economic life of the Islamic community during the reign of Caliph Umar was the majority of economic activities with trade, agriculture, and industry. The policies of Caliph 'Umar bin al-Khathtab in the economic field include: the establishment of baitul mal, land ownership, Zakat, usyur, currency, sodaqah for non-Muslims, classification and allocation of state income. and The influence of 'Umar's economic policy cannot be separated from several factors: 'Umar's concern about economic issues, using deliberation in making every policy that is set, prioritizing the benefit of the people, and 'Umar is a responsible and ascetic person.